The Significance of Pre-Marital Education and Post-Marital Counseling in Minimizing Divorce Rates - Eva Nur Hopipah; Ulfiah (CV. Doki Course and Training, 2025)
The increasing divorce rate from time to time raises concern among professionals and researchers in the field of family mental and physical health. This study specifically aims to explore the urgency and effectiveness of pre-marital education and post-marital counseling in minimizing divorce, particularly among couples with relatively young marital ages and short marriage durations. The focus is to understand how preparation before marriage and mediation after marriage can influence the stability of a household. This study uses a qualitative method with a case study approach. Data were collected through observation, in-depth interviews, and documentation techniques. The research was conducted over a five-month period, from January to June 2023, involving 24 individuals from Bandung City who had experienced or were in the process of divorce. These individuals were selected purposively based on the criteria of having multiple divorce cases and a marriage duration of less than five years. The findings revealed that only one of the 24 subjects had received structured pre-marital education before deciding to marry. Meanwhile, all participants underwent post-marital counseling sessions due to conflicts and emotional crises within their marriages. Most of the subjects reported a lack of readiness, poor conflict resolution skills, and minimal knowledge about marital responsibilities. The study concludes that pre-marital education plays a crucial role in mental and emotional preparedness, while post-marital counseling serves as an essential curative strategy to resolve disputes. Therefore, structured educational and counseling programs are strongly recommended to prevent premature divorce and strengthen marital resilience.